30‐day patient reported outcomes can be predicted by change in left atrial pressure and not change in transmitral gradient following MitraClip. Issue 6 (27th January 2021) - Pierre, Keniel; Adedinsewo, Demilade A.; Al‐Hijji, Mohammed; Miranda, William R.; Alkhouli, Mohamad; Eleid, Mackram F.; Guerrero, Mayra; Pollak, Peter M.; Rihal, Charanjit S.; El Sabbagh, Abdallah
Abstract: Background: Change in left atrial pressure (LAP) has been shown to be associated with symptom improvement post‐MitraClip; however, the association between acute procedural changes in transmitral diastolic mean gradient (MG) compared to LAP and symptom improvement is not well established. Methods: 164 consecutive patients undergoing MitraClip at Mayo Clinic between June 2014 and May 2018 were included. Preclip and postclip MG and LAP were recorded. Baseline demographics, clinical, and echocardiographic outcomes, including 30‐day New York Heart Association (NYHA) functional status were obtained from patient charts. Results: Median age was 81.5 years (IQR: 76.3, 87), 34% were female and 94.5% had NYHA class III and IV functional status at baseline. At baseline, median MG was 4 mmHg (IQR: 3, 5) and LAP was 19 mmHg (IQR: 16, 23.5). Following MitraClip deployment, the median MG was 4 mmHg (IQR: 3, 6) and the median LAP was 17 mmHg (IQR: 14, 21), 69.5% of patients had less than moderate MR. There was no statistically significant association between change in MG and NYHA functional class at 30 days (OR = 0.95, 95% CI: 0.76–1.20). However, a reduction in LAP following MitraClip deployment was significantly associated with improvement in NYHA functional status at 30 days following adjustments for age and sex (aOR 3.36, 95% CI: 1.34–8.65). There was no significant correlation between change in mean LAP and change in MG ( p = .98). Conclusion: Unlike change in left atrial pressure, change in MG post‐MitraClip was not associated with patient reported outcomes at 30 days and did not correlate with change in left atrial pressure. Long‐term follow up is needed to evaluate the impact of LA pressure on symptoms.